Prognostic impact of repeat sentinel lymph node biopsy in patients with ipsilateral breast tumour recurrence. Issue 5 (25th March 2019) - Poodt, I G M; Vugts, G; Schipper, R J; Roumen, R M H; Rutten, H J T; Maaskant-Braat, A J G; Voogd, A C; Nieuwenhuijzen, G A P; Luiten, E J T; Rutgers, E J T; Vrancken-Peeters, M T F D; Bessems, M; et al.
Abstract: Background: Ipsilateral breast tumour recurrence (IBTR) has an unfavourable prognosis, with a significant subsequent risk of distant recurrence. Repeat sentinel lymph node biopsy (rSLNB) has recently been demonstrated to be technically feasible and useful in tailoring adjuvant treatment plans in patients with IBTR. The prognostic impact of rSLNB in patients with IBTR remains unclear. This study analysed the risk of distant recurrence after IBTR, and evaluated the prognostic impact of rSLNB and other patient and tumour characteristics on distant recurrence-free survival. Methods: Data were obtained from the SNARB (Sentinel Node and Recurrent Breast Cancer) study. Cox proportional hazards analyses were performed to assess the prognostic effect of tumour, patient and treatment factors on distant recurrence-free survival. Results: Of the 515 included patients, 230 (44·7 per cent) had a tumour-negative rSLNB and 46 (8·9 per cent) a tumour-positive rSLNB. In 239 patients (46·4 per cent) the rSLNB procedure was unsuccessful. After a median follow-up of 5·1 years, 115 patients (22·3 per cent) had developed a recurrence. The overall 5-year distant recurrence-free survival rate was 84·2 (95 per cent c.i. 80·7 to 87·7) per cent. An interval of less than 2 years between primary breast cancer treatment and ipsilateral recurrence ( P =  0·018), triple-negative IBTR ( P =  0·045) and absence of adjuvant chemotherapy after IBTR ( P =  0·010) were independently associated with poor distant recurrence-free survival. The association between the outcome of rSLNB and distant recurrence-free survival was not statistically significant ( P = 0·682). Conclusion: The outcome of rSLNB is not an important prognostic factor for distant recurrence, and its value as a staging tool in patients with IBTR seems disputable. Abstract : No impact